RANCANG BANGUN PRODUKSI KOPI ANGGOTA KOPERASI BAITUL QIRADH BABURRAYYAN MENGGUNAKAN GAMBAS - Ira Zulfa (STEKOM PRESS, 2020)
One of the survey activities carried out at the Baitul Giradh Baburrayyan Cooperative was regarding the coffee production of members who are members of the Baitul Oiradh Baburrayyan Cooperative organization, which aims to speed up the data processing process and make it easier to produce reports on production. To carry out these activities quickly and precisely, it is necessary to make an application as a tool in the data processing and presentation of data that will be needed by data users. This data processing application is made using the gambas programming language.